Teachers’ Unions: Cadres of Political Parties or Distinct Curriculum Ideologies? - Ghimire, Shurendra (BMC Journal of Scientific Research, 2024)
School teachers as professionals have been segregated into different trade unions in Nepal. The basis of this separation is whether on distinct curriculum ideology of professionals or just a grouping of the caders of different political parties has not been empirically assessed yet, however, common understanding is the later. As the educational quality is influenced by teachers’ consciousness and ideology, the study captured their curriculum ideology by employing the qualitative survey methodology. A set of five questions was developed to explore put their views, and thus obtained views of 16 teachers who are active in three largest trade unions were coded and tabulated. I got insight in three aspects from the thematic analysis of the information. First, the teachers how long they have been in leading positions did not answer the questions, only those who were already familiar to me replied. This indicates that leader teachers are not confident to put their curriculum ideology forward. Second, those teachers who shared their views were unable to present a comprehensive curriculum ideology. Last, there is no distinctness in curriculum ideology as they are affiliated to the distinct trade unions. This study concludes that teachers’ partition in different trade unions is just an affiliation to the political party instead of cultivating and promoting a distinct curriculum ideology.